ANALISIS SEMANTIK POSTER EDUKASI VIRUS CORONA DI MEDIA SOSIAL - Oky Yahya Aprilia (Balai Bahasa Sumatera Utara, 2022)
This study aims to explain the semantic meaning of the coronavirus education poster on social media. The problem of this study is how the semantic meaning is represented in the coronavirus education poster.This study used a qualitative descriptive method with Abdul Chaer's semantic theory to analyze coronavirus education posters on social media. Furthermore, the method of collecting the data used documentation techniques. Data analysis in this study uses a semantic study and refers to the semantic theory of Abdul Chaer (2009).The results of this study showed that there were three forms of lexical meaning including verbs as many as 33 words, lexical nouns 25 words, lexical adjectives 19 words, and the others are connecting words, pronouns, and adverbs. On the other hand, there were three grammatical forms, consisted of verbs, nouns, and adjectives. Besides, it had contextual meanings that were closely related to the COVID-19 case, for example, masks, paramedics, family portraits, farming, washing hands, and crowd illustrations.